Method for controlling properties of biological silicon oxide

By impregnating and removing inorganic impurities on siliceous plant matter before heat treatment, controlling the amount and type of non-siliceous inorganic substances, the problem of incomplete removal of impurities during the extraction process of amorphous silicon oxide in the prior art is solved, and the production of high-quality amorphous silicon oxide is achieved.

CN120172416APending Publication Date: 2025-06-20KILT LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510480294.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-08-23
Filing Date
2019-08-26
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

In the prior art, when extracting amorphous silicon oxide from silic plant substances, it is difficult to effectively remove carbon and inorganic impurities, resulting in a decrease in the porosity, pore volume and pore size of the silicon oxide, and may cause melting of the silicon oxide and undesirable crystallization during the heat treatment.

Method used

The content of hydrocarbons and inorganic compounds is reduced by impregnating the silic plant matter in water, separating the impregnated water and treating the solids before heat treatment. The heat treatment is then performed in the presence of oxygen, and the amount and type of non-silic inorganic substances are controlled to produce porous amorphous silicon oxide with desired properties.

Benefits of technology

Amorphous silicon oxide with desired surface area, pore volume, pore size, abrasive and dispersible properties is achieved from biological sources, avoiding melting of silicon oxide and undesirable crystallization, while reducing the emission of nitrogen oxides and sulfur during heat treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120172416A_ABST
    Figure CN120172416A_ABST
Patent Text Reader

Abstract

The invention relates to a method for controlling the properties of biological silicon oxide. Porous amorphous silicon oxide can be obtained from siliceous plants containing non-siliceous inorganic materials. The siliceous plant material is soaked in an aqueous solution comprising a chelating agent. The chelating agent is present in an amount that contributes to extraction of at least some of the non-siliceous inorganic materials. The aqueous solution is then separated from the siliceous plant material. The siliceous plant is imparted beneficial properties by controlling the amount of at least one preselected non-siliceous inorganic substance in the siliceous plant. At the end of the process, the siliceous plant material is heat treated in the presence of oxygen at a temperature to produce the resulting amorphous silicon oxide with beneficial properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross - reference to related applications

[0002] This application is a divisional application of Chinese Patent Application No. 201980058043.6 (corresponding International Application No. PCT / US2019 / 048108) with the earliest priority date of September 5, 2018 and the invention title of "Method for Controlling the Properties of Biogenic Silicon Oxide".

[0003] This patent application claims the benefit of priority of U.S. Provisional Patent Application Serial No. 62 / 830,054, filed on April 5, 2019, and U.S. Provisional Patent Application Serial No. 62 / 727,183, filed on September 5, 2018, and this application claims the priority of U.S. Patent Application Serial No. 16 / 549,667, filed on August 23, 2019, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The disclosed and claimed invention relates to a method for controlling the properties of biogenic silicon oxide. More specifically, the invention presented herein relates to methods for selectively enhancing the desired properties of amorphous silicon oxide recovered from renewable resources of siliceous plants, including rice husks, stems, and leaves. Background Art

[0005] Amorphous silica is currently manufactured, sold, and utilized for a variety of purposes. U.S. Patents US 6,406,678, US 7,270,794, and Shipley's U.S. Patent US 8,057,771 (each incorporated herein by reference) disclose methods for recovering amorphous silica from biological sources such as rice husks. Amorphous silica exists in siliceous plant material in a lattice structure, closely intertwined with various organic compounds such as cellulose, lignin, hemicellulose, and various inorganic substances including phosphates, salts, gels, hydrates, and oxides. Typical inorganic substances in rice husk compositions are elements or various compounds of phosphorus, potassium, calcium, magnesium, manganese, sodium, iron, zinc, and aluminum. Removing these organic and inorganic substances by washing or chelation followed by heat treatment to leave substantially pure amorphous silica with high porosity (as it exists in the plant material) is problematic. If the plant material is heat-treated at low temperatures, removal of carbon and organic impurities is usually incomplete. Heat treatment at any temperature generally does not remove all carbon. Heat treatment at any temperature has little effect on inorganic impurities. Heat treatment at higher temperatures causes fluxing of the lattice structure of the silica, thereby reducing its porosity (effective surface area per unit weight), pore volume, and pore diameter, while trapping impurities within the structure. Heat treatment at even higher temperatures causes undesirable crystallization of the silica. Heat treatment alone can scarcely remove inorganic impurities. If the silica is fluxed during heat treatment, post-heat-treatment removal of inorganic impurities from the silica is problematic.

[0006] U.S. Patents US 6,406,678; US 7,270,794, and US 8,057,771 disclose an apparatus by which amorphous silica having selected properties (including the amounts of carbon, inorganic impurities, and porosity) can be extracted; lignin, hemicellulose, cellulose-derived sugars, and available energy (open-loop renewable energy) can also be extracted from siliceous plant material (such as rice husks, straw, and leaves) in an environmentally friendly manner (without carbonizing the atmosphere, reducing nitrogen oxide and sulfur emissions, and not involving the use of toxic or polluting chemicals).

[0007] Depending on the nature and quality of the desired end product, prior to heat treatment, the siliceous plant material can be impregnated in water, the impregnation water separated, and the solid treated to effect reduction of hydrocarbons and / or removal of inorganic compounds. Lignin, hemicellulose, and cellulose-derived sugars can be recovered from the water used for impregnating and / or soaking the siliceous plant material. Heat treatment of the solid in the presence of oxygen produces siliceous ash. By varying the steps prior to heat treatment and the temperature of the heat treatment, the siliceous ash produced may have no detectable crystal content or selectively contain more or less amorphous silica or crystalline silica, more or less carbon, more or less inorganic residue, and have the desired porosity.

[0008] The processing steps before heat treatment may optionally include: impregnation in water; removal of the impregnation water; reduction of the solid organic compounds by immersion in an aqueous solution containing an oxidizing solute; extraction of the solid inorganic compounds by immersion in an aqueous solution containing a chelating agent, an inorganic acid, and / or an organic acid; and rinsing and drying the solid. Then, in the presence of oxygen, typically at a temperature below that which causes the formation of crystalline silica, an exothermic heat treatment is performed on the remaining solid. The removal of impurities significantly increases the temperature at which the crystalline structure forms. The energy from the heat treatment can be captured for beneficial use, including the generation of electrical energy. After heat treatment, the resulting siliceous ash (containing amorphous silica) can be washed with water and / or subjected to various chelation and / or chemical rinses to remove more impurities. Lignin, hemicellulose, and cellulose-derived sugars can be recovered from the impregnation water. By removing lignin, hemicellulose, and cellulose-derived sugars before heat treatment, the emissions of nitrogen oxides and sulfur from the heat treatment can be reduced. Summary of the Invention

[0009] It has been found that desired properties of amorphous silica derived from biological sources such as rice husks can be obtained by manipulating the quantity and nature of impurities in the plant material before heat treatment. By selecting the quantity and type of flux agent retained in the plant material, amorphous silica with desired surface area, pore volume, pore size, abrasiveness, and dispersibility properties can be produced.

[0010] Porous amorphous silica can be prepared from siliceous plant material containing non-siliceous inorganic matter by first immersing the siliceous plant material in an aqueous solution comprising a chelating agent present in an amount sufficient to extract at least some of the non-siliceous inorganic matter. The siliceous plant material is separated from the aqueous solution, and the amount of a preselected non-siliceous inorganic matter in the siliceous plant material is controlled to impart beneficial properties to the siliceous plant material. Finally, the siliceous plant material is heat-treated in the presence of oxygen at a certain temperature, wherein amorphous silica in a porous form is produced.

[0011] The methods described herein are directed to the beneficial use of siliceous plant material (such as rice husks, rice straw, and leaves) to produce various products such as silica, lignin, and hemicellulose, cellulose-derived sugars, and usable energy, which do not carbonize the atmosphere, reduce the emissions of nitrogen oxides and sulfur, and do not use irritating, polluting chemicals.

[0012] In a process for producing amorphous silica from siliceous plant material comprising inorganic and organic compounds, the siliceous plant material is soaked in an aqueous solution of citric acid, other chelating agents, and / or inorganic acids. The presence of the chelating agents and / or inorganic acids in an amount sufficient to extract at least some of the inorganic and organic compounds. The siliceous plant material is separated from the aqueous solution. The siliceous plant material is then heat-treated in the presence of oxygen such that the resulting silica is in amorphous form. The removal of the inorganic compounds can be controlled by the amounts of the chelating agents, inorganic acids, and other variables such as temperature, time, and the removal process using washing. For a given final content of inorganic material in the silica matrix, the heat-treatment temperature can be manipulated to give the specific surface area, pore characteristics, and dispersibility of the silica.

[0013] The present invention offers several advantages over existing methods for producing biosilica. By assessing the amount of non-siliceous inorganic material present in a given feedstock, the amount of chelating agent required to achieve a specific impurity concentration can be predetermined. The present invention provides a more effective and potentially greater reduction of non-siliceous inorganic material during the chelation step. For a fixed heat-treatment temperature value, the present invention can be used to produce various amorphous silica products with a variety of controlled specific surface areas, pore volumes, pore sizes, abrasiveness, and dispersibility by controlling the content of non-siliceous inorganic material (which acts as a flux during heat-treatment and causes disintegration of the silica matrix) in the biological source. By controlling the heat-treatment temperature in the presence of oxygen, the present invention can be used to produce various silica products with a variety of specific surface areas, pore volumes, pore sizes, abrasiveness, and dispersibility. The present invention allows for post-treatment of the silica to further reduce the content of inorganic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a graph showing the experimental results demonstrating the ability to control the surface area of biosilica by controlling the total content of non-siliceous inorganic material (flux) retained in the rice husk composition.

[0015] Figure 2 is a graph showing the experimental results demonstrating the ability to control the pore characteristics of biosilica by controlling the non-siliceous inorganic material (flux) retained in the rice husk composition. DETAILED DESCRIPTION

[0016] While the invention will be described with reference to preferred embodiments, those skilled in the art will understand that various changes can be made and elements thereof can be replaced with equivalents without departing from the scope of the invention. Additionally, many modifications can be made to adapt a particular situation or material to the teachings of the invention without departing from the essential scope thereof. Accordingly, it is intended that the invention not be limited to the particular embodiments disclosed as the best mode contemplated for carrying out the invention, but that the invention will include all embodiments within the scope of the appended claims and their legal equivalents.

[0017] Porous amorphous silica can be obtained from siliceous plant material containing non-siliceous inorganic matter. In prior practice, the non-siliceous inorganic matter would be removed during the soaking and chelating steps. It has been found that if certain non-siliceous inorganic matter is preferentially retained within the plant material prior to heat treatment, preferred properties can be imparted to the resulting amorphous silica.

[0018] In a currently preferred method, the siliceous plant material is soaked in an aqueous solution containing a chelating agent. The chelating agent is present in an amount to extract at least some of the non-siliceous inorganic matter. The aqueous solution is then separated from the siliceous plant material. By controlling the amount of at least one preselected non-siliceous inorganic matter in the siliceous plant material, beneficial properties can be imparted to the siliceous plant material. At the end of the process, the siliceous plant material is heat treated at a certain temperature in the presence of oxygen, wherein the resulting silica comprises silica in a porous amorphous form.

[0019] The preselected non-siliceous inorganic matter can include any or all of the following materials: elements or compounds of alkali metals (most preferably lithium, sodium, and potassium), alkaline earth metals (most preferably magnesium and calcium), aluminum, boron, iron, manganese, titanium, or phosphorus.

[0020] One method of controlling the amount of the preselected non-siliceous inorganic matter is to control the amount of chelating agent in the siliceous material. Suitable chelating agents include citric acid, acetic acid, ethylenediamine, ethylenediaminetetraacetic acid, dimercaptosuccinic acid, trimethylamine tricarboxylic acid, α-lipoic acid, and diethylenetriaminepentaacetic acid. Preferably, the amount of the chelating agent is maintained between 0.001 kilograms per kilogram of plant material and 1 kilogram per kilogram of plant material. In the case of the citric acid chelating agent, the amount of citric acid is preferably in the range of 0.01 kilograms per kilogram of plant material to 0.1 kilograms per kilogram of plant material. By controlling the amount of chelating agent present in the plant material, the amount of non-siliceous inorganic matter remaining in the plant material can be determined to be a preselected amount sufficient to impart desired properties to the silica produced from the heat treatment of the plant material.

[0021] An alternative method of controlling the amount of preselected non-siliceous inorganic substances is to introduce an inorganic acid to cooperate with the siliceous plant substances. Suitable inorganic acids include sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, boric acid, and perchloric acid. The inorganic acid will help extract some of the non-siliceous inorganic substances, and a part remains in the plant substances. The remaining non-siliceous inorganic substances are selected to impart desired properties to the silica produced by the heat treatment of the plant substances.

[0022] Another method of controlling the amount of preselected non-siliceous inorganic substances is to control the amount of chelating agent added to the aqueous solution when soaking the plant substances. It has been found that by controlling the amount of chelating agent added to the aqueous solution, the amount of preselected inorganic non-siliceous substances can be manipulated within the range of 20 ppm to 25,000 ppm, and more preferably within the range of 300 ppm to 15,000 ppm.

[0023] Another method of controlling the amount of preselected non-siliceous inorganic substances is to add the desired amount of preselected non-siliceous inorganic substances back to the plant substances in an amount sufficient to impart desired properties to the silica once the plant substances have been heat treated.

[0024] Another method of controlling the amount of preselected non-siliceous inorganic substances is to add the desired amount of preselected non-siliceous inorganic substances back to the plant substances in an amount sufficient to impart desired properties to the silica once the plant substances have been heat treated. It has been found that alkali metals (more specifically lithium, sodium, and potassium) have a strong influence on the properties of silica; an increase in the amount of these alkali metals results in a decrease in surface area and pore volume when compared to the control. It has also been found that alkaline earth metals (more specifically magnesium and calcium) will have a mild influence on the properties of silica; an increase in the amount of these elements also results in a decrease in surface area and pore volume. Finally, it has been found that other typical inorganic impurities do not affect the properties of silica (more specifically boron, zinc, aluminum, manganese, phosphorus, and iron).

[0025] One of the properties of amorphous silica that can be controlled using the method of the present invention is the surface area of the silica. It has been found that the surface area of amorphous silica can be controlled within a narrow range within the relatively wide range of 10 m 2 / g to 450 m 2 / g, and more preferably within a narrow range within the relatively wide range of 30 m 2 / g to 400 m 2 / g.

[0026] Another property of amorphous silica that can be controlled using the method of the present invention is the pore volume of the silica. It has been found that the pore volume of amorphous silica can be controlled within a narrow range within the relatively wide range of 0.50 cc / g to 0.05 cc / g, and more preferably within a narrow range within the relatively wide range of 0.40 cc / g to 0.10 cc / g.

[0027] Another property of the amorphous silica that can be controlled using the method of the present invention is the pore size of the silica. It has been found that the pore size of the amorphous silica can be controlled within a narrow range within a relatively wide range of 10 Å to 200 Å, more preferably within a narrow range within a relatively wide range of 30 Å to 100 Å.

[0028] It has been found that the content of non-siliceous inorganic substances in the heat-treated silica can be controlled within the range of 10 ppm to 1000 ppm, and more preferably within the range of 100 ppm to 500 ppm, by post-cleaning the silica with at least one of water, inorganic acids, chelating agents, and pH-adjusting chemicals.

[0029] The preferred heat treatment temperature is within the range of 200 °C to 1000 °C.

[0030] Certain aspects of the present invention are demonstrated in the following experiments.

[0031] Experiment 1

[0032] Several tests were conducted using the same mixing system, which included a top-entry mechanical mixer, a hot plate (preferably with temperature feedback), and a 2-liter capacity beaker. One test was a control, and the other tests used different citric acid chelating agent concentrations. The test procedure was as follows:

[0033] 1. Each beaker was filled with 1800 ml of distilled water at 160 °F.

[0034] 2. 100 grams of 60-mesh ground rice husk (from the same sample batch) was added to each beaker, and the mixer was run at the same speed. The hot plate was set to the same (low) heating level, or to 160 °F if they had a feedback mechanism.

[0035] 3. The control batch was filtered to remove water, post-dried at 50 °C, and heat-treated at 600 °C. The inorganic element content of the silica was analyzed.

[0036] 4. The other batches were treated with increasing amounts of 10% citric acid solution, allowing time for proper chelation, followed by a series of pure water soaking and draining cycles. 30% hydrogen peroxide solution was added to the previous cycle for final washing. The materials from the tests were filtered to remove water, post-dried at 50 °C, and heat-treated at 600 °C. The inorganic element content of the silica was analyzed.

[0037] Once the residual inorganic elements of the treated rice husk samples were analyzed by ICP, the relative removal rates for each treatment were compared. The results of the comparison are shown in Table 1 below:

[0038] Table 1

[0039]

[0040] As shown in Table 1, increasing amounts of citric acid will improve the removal of inorganic substances. It is assumed that 1 mole of citric acid will chelate 1 mole of the element to simulate the removal. Therefore, for a given feedstock, using a specific amount of citric acid concentration can achieve a specific inorganic element concentration, especially the fluxing elements (such as K, Na, Ca, Mg) that will affect the properties of the final silica product such as surface area, pore volume, pore size, and dispersibility.

[0041] Experiment 2

[0042] Experiments were conducted to determine other ways to further reduce inorganic substances during the chelation step. Four tests were carried out using the same mixing system, which included a top-entering mechanical mixer, a hot plate (preferably with temperature feedback), and a 2-liter capacity beaker. One test was a control, and the other tests used the same concentration of citric acid chelating agent. One test introduced an inorganic acid during chelation, and another test introduced an inorganic acid during the soaking step before the chelation step to further lower the pH of the solution. The test procedure is as follows:

[0043] 1. Each beaker was filled with 1800 ml of distilled water at 160°F.

[0044] 2. 100 grams of +60 mesh ground rice husk (from the same sample batch) was added to each beaker, and the mixer was run at the same speed. The hot plate was set to the same (low) heating level, or to 160°F if they had a feedback mechanism.

[0045] 3. The control batch was filtered to remove water, post-dried at 50°C, and heat-treated at 600°C. The inorganic element content of the silica was analyzed.

[0046] 4. The second batch was treated with a 10% citric acid solution, allowed time for proper chelation, followed by a series of pure water soaking and draining cycles. A 30% hydrogen peroxide solution was added to the previous cycle for final washing. The material from the test was filtered to remove water, post-dried at 50°C, and heat-treated at 600°C. The inorganic element content of the silica was analyzed.

[0047] 5. The third batch was treated with a 10% nitric acid solution, 50% of the total 30% hydrogen peroxide solution, and a 10% citric acid solution, allowed time for proper chelation, followed by a series of pure water soaking and draining cycles. The remaining 50% of the 30% hydrogen peroxide solution was added to the previous cycle for final washing. The material from the test was filtered to remove water, post-dried at 50°C, and heat-treated at 600°C. The inorganic element content of the silica was analyzed.

[0048] 6. In the initial soaking step, the fourth batch is treated with 10% nitric acid solution and 50% of the total hydrogen peroxide solution. This soaking step is carried out before chelation. After soaking, there is a chelation step with 10% citric acid solution, and a series of pure water soaking and draining cycles. The remaining 50% of the 30% hydrogen peroxide solution is added to the previous cycle for final washing. The material from the test is filtered to remove water, post-dried at 50 °C, and heat-treated at 600 °C. The inorganic element content of the silica is analyzed.

[0049] Once the residual inorganic element impurities of the treated rice husk samples are analyzed by ICP, the relative removal rates for each treatment are compared. The results of the comparison are shown in Table 2 below:

[0050] Table 2

[0051]

[0052] As shown in Table 2, adding inorganic acid during the chelation process or during the pre-soaking process before chelation to promote pH change will increase the amount of inorganic matter removed from the rice husk. Note that in this example, citric acid buffers the pH of the solution to 3, and the inorganic acid will contribute to further reducing the pH to 2. It can be seen from the test results that further purification of silica can be achieved by various washing methods, with or without chemical reagents and within a temperature range.

[0053] Experiment 3

[0054] Experiments were conducted to determine the ability to control the surface area, pore characteristics, and dispersibility by controlling the flux level on the rice husk composition. In current practice, the goal is to remove as completely as possible the inorganic substances that can act as fluxes before combustion to produce a high surface area and good dispersibility. Controlling the level of residual inorganic matter in the rice husk will provide a lower surface area and a greater degree of abrasiveness. Since the quality of silica may also be affected by the combustion temperature, a combustion temperature of 600 °C was used for all evaluations.

[0055] Several samples of each batch were heat-treated at 600 °C, with different concentrations of inorganic element impurities that can act as fluxes (expressed as the sum of Na, K, Ca, and Mg). The fluxes (Na, K, Ca, and Mg), surface area, and pore volume of the silica were analyzed. The results are plotted in Figure 1 and 2 the coordinate plots shown:

[0056] As can be seen from the test results, at a given heat treatment temperature, with a specific flux element concentration, silica properties such as surface area, pore volume, and pore diameter can be obtained, leading to other important properties such as dispersibility and abrasiveness.

[0057] Experiment 4

[0058] Experiments were conducted to evaluate the changes in surface area, pore volume, and pore diameter of a given batch of treated rice husks using specific flux (expressed as the sum of Na, K, Ca, and Mg) content levels. The treated rice husk batches were heat-treated at four different temperatures, and the results are shown in Table 3 below:

[0059] Table 3

[0060]

[0061] As can be seen from the test results, the given treated rice husks will produce different results in pore volume, surface area, and pore diameter at different heat treatment temperatures, and then the desired properties of a specific final product can be manipulated.

[0062] Experiment 5

[0063] Experiments were conducted to evaluate the effect of post-washing the silica to further remove metals and achieve a higher degree of purification.

[0064] Several tests were conducted using the same mixing system including a magnet, a hot plate (preferably with temperature feedback), and a 500 ml capacity beaker. One test was a control, while the other tests used different citric acid chelation concentrations. The test procedure was as follows:

[0065] 1. Each beaker was filled with 300 ml of distilled water at 160°F.

[0066] 2. 30 grams of silica (from the same sample batch) was added to each beaker, and the mixer was run at the same speed. The hot plate was set to the same (low) heating level, or 160°F if they had a feedback mechanism.

[0067] 3. The metal content of the control silica was analyzed.

[0068] 4. Other batches were treated with increasing amounts of 10% citric acid solution, and then one of the pure water soaking and draining cycles was performed. The materials from the tests were filtered to remove water and post-dried at 50°C. The inorganic element impurity content of the silica was analyzed.

[0069] The comparison results are shown in Table 4 below:

[0070] Table 4

[0071]

[0072] These test results indicate that the residual inorganic substances in silica can be further reduced, thereby generating impurity levels for each market application requirement.

[0073] Experiment 6

[0074] Some tests were conducted using a process of reintroducing the desired inorganic elements into a control pre-treated rice husk sample from which most of the inorganic contaminants had been removed. The inorganic contaminants (usually from a salt solution with a given concentration) were sprayed onto the dry rice husk sample under vigorous stirring to fully incorporate and wet the rice husk. Based on the number of elements in each solution and the amount of silica on each rice husk sample, the concentration of the desired contaminants was calculated. Wetting was calculated in the following way: the rice husk was able to absorb all the excess moisture, making the distribution of elemental impurities uniform.

[0075] The wet samples were post-dried in an oven and then calcined at different temperatures to evaluate the surface area and pore volume. The experimental results are shown below:

[0076] Lithium hydroxide solution was incorporated into the control rice husk sample with three different concentration targets measured on the calcined silica sample: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 5 below:

[0077] Table 5

[0078]

[0079] The results in Table 5 indicate that the increased amount of lithium in the rice husk has a significant effect on reducing the surface area and pore volume of the calcined silica sample.

[0080] Potassium hydroxide solution was incorporated into the control rice husk sample with three different concentration targets measured on the calcined silica sample: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 6 below:

[0081] Table 6

[0082]

[0083] The results in Table 6 indicate that the increased amount of potassium in the rice husk has a significant effect on reducing the surface area and pore volume of the calcined silica sample.

[0084] Sodium hydroxide and sodium sulfate solutions were incorporated into the control rice husk sample with three different concentration targets measured on the calcined silica sample: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 7 below:

[0085] Table 7

[0086]

[0087] The results in Table 7 show that the increased sodium content in rice husk has a significant effect on reducing the surface area and pore volume of the calcined silica samples.

[0088] Calcium oxide solution was incorporated into the control rice husk samples with three different concentration targets measured on the calcined silica samples: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 8 below:

[0089] Table 8

[0090]

[0091] The results in Table 8 show that the increased calcium content in rice husk has a moderate effect on reducing the surface area and pore volume of the calcined silica samples.

[0092] Magnesium sulfate solution was incorporated into the control rice husk samples with three different concentration targets measured on the calcined samples: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 9 below:

[0093] Table 9

[0094]

[0095] The results in Table 9 show that the increased magnesium content in rice husk has a moderate effect on reducing the surface area and pore volume of the calcined silica samples.

[0096] Boric acid and zinc sulfate solutions were incorporated into the control rice husk samples with three different concentration targets measured on the calcined samples: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 10 below:

[0097] Table 10

[0098]

[0099] The results in Table 10 show that the increased boron and zinc content in rice husk has some effect on the surface area and pore volume, however the results do not show any trend.

[0100] Aluminum sulfate and manganese sulfate solutions were incorporated into the control rice husk samples with three different concentration targets measured on the calcined samples: 1000 ppm, 2000 ppm, and 3000 ppm. The results of this experiment are shown in Table 11 below:

[0101] Table 11

[0102]

[0103] The results in Table 11 show that aluminum and manganese have no effect on the properties of calcined silica.

[0104] Although the foregoing description contains certain details, these details should not be construed as limitations on the scope of the invention, but rather as examples of a preferred embodiment thereof. Accordingly, the scope of the invention should be determined not by the embodiments shown, but by the appended claims and their legal equivalents.

Claims

1. A method for preparing porous amorphous silica with a controlled surface area, said porous amorphous silica being derived from siliceous plant material containing at least one flux, said at least one flux being selected from non-siliceous inorganic materials containing lithium, potassium, sodium, calcium or magnesium, the method comprising the following steps: (a) Heat-treat the siliceous plant material at a certain temperature in the presence of oxygen, wherein the silica produced includes silica in a porous amorphous form. Wherein the amount of the at least one flux in the siliceous plant material and the heat treatment temperature are controlled to produce amorphous silica having a controlled surface area within a specific narrow band in the range of 10 m 2 / g to 450 m 2 / g, and wherein the amount of the at least one flux in the siliceous plant material is controlled by mixing a desired amount of the at least one flux into the siliceous plant material, thereby establishing the amount of the at least one flux retained in the plant material at a preselected amount of 20 ppm to 25,000 ppm.

2. The method of claim 1, wherein the amount of said at least one flux in said siliceous plant material is manipulated by controlling the amount of chelating agent added to said siliceous plant material.

3. The method of claim 2, wherein said chelating agent is selected from citric acid, acetic acid, ethylenediamine, ethylenediaminetetraacetic acid, dimercaptosuccinic acid, trimethylamine tricarboxylic acid, α-lipoic acid and diethylenetriaminepentaacetic acid.

4. The method of claim 3, wherein the amount of said chelating agent is from 0.001 kg to 1 kg per kg of plant material.

5. The method of claim 4, wherein said chelating agent is citric acid and the amount of citric acid is from 0.01 kg to 0.1 kg per kg of plant material.

6. The method of claim 1, wherein the amount of said at least one flux in said siliceous plant material is controlled by introducing at least one inorganic acid into said siliceous plant material.

7. The method of claim 6, wherein said at least one inorganic acid is selected from sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, boric acid and perchloric acid.

8. The method of claim 2, wherein the amount of said at least one flux can be controlled within a specific narrow range of 20 ppm to 25000 ppm.

9. The method of claim 1, wherein the surface area of said amorphous silica is controlled within a specific narrow range of 30 m 2 / g to 400 m 2 / g by controlling the amount of said at least one flux in said siliceous plant material and the heat treatment temperature.

10. The method of claim 1, wherein the pore volume of said amorphous silica is controlled within a specific narrow range of 0.50 cc / g to 0.05 cc / g by controlling the amount of said at least one flux in said siliceous plant material and the heat treatment temperature.

11. The method of claim 10, wherein the pore volume of said amorphous silica is controlled within a specific narrow range of 0.40 cc / g to 0.10 cc / g by controlling the amount of said at least one flux in said siliceous plant material and the heat treatment temperature.

12. The method of claim 1, wherein the pore size of the amorphous silica is controlled within a specific narrow range of 10 angstroms to 200 angstroms by controlling the amount of at least one flux in the siliceous plant material and the heat treatment temperature.

13. The method of claim 12, wherein the pore size of the amorphous silica is controlled within a specific narrow range of 30 angstroms to 100 angstroms by controlling the amount of at least one flux in the siliceous plant material and the heat treatment temperature.

14. The method of claim 1, wherein the amount of at least one flux in the siliceous plant material is controlled within a specific narrow band in the range of 300 ppm to 15000 ppm.

15. The method of claim 1, wherein the content of at least one flux in the heat-treated silica is controlled within a specific narrow band in the range of 10 ppm to 1000 ppm by post-washing the silica with at least one of water, inorganic acid, chelating agent, and pH-adjusting chemical.

16. The method of claim 15, wherein the content of at least one flux in the heat-treated silica is controlled within a specific narrow band in the range of 100 ppm to 500 ppm by post-washing the silica with at least one of water, inorganic acid, chelating agent, and pH-adjusting chemical.

17. The method of claim 1, wherein the heat treatment temperature is in the range of 200 °C to 1000 °C.

18. The method of claim 1, wherein the at least one flux in the siliceous plant material comprises at least one of the following: lithium, sodium, potassium, magnesium, calcium, aluminum, boron, iron, manganese, titanium, or phosphorus.

19. The method of claim 1, wherein the amount of the at least one flux in the siliceous plant material is chemically controlled.

20. The method of claim 1, wherein the amount of at least one flux and the heat treatment temperature are controlled to prevent the formation of a crystalline structure in the amorphous silica.

21. A method for preparing porous amorphous silica from siliceous plant material containing non-siliceous inorganic substances, the method comprising the following steps: (a) Immerse the siliceous plant material in an aqueous solution containing a chelating agent, wherein the chelating agent is present in an amount to extract at least some of the non-siliceous inorganic substances. (b) Separate the siliceous plant material from the aqueous solution. (c) Control the amount of at least one preselected non-siliceous inorganic substance in the siliceous plant material by mixing a desired amount of the preselected non-siliceous inorganic substance into the siliceous plant material, thereby establishing the amount of the preselected non-siliceous inorganic substance retained in the plant material at a preselected amount from 20 ppm to 25000 ppm, the at least one preselected non-siliceous inorganic substance being selected from non-siliceous inorganic substances comprising lithium, potassium, sodium, calcium, or magnesium, and selecting the at least one preselected non-siliceous inorganic substance to impart beneficial properties to the siliceous plant material; and (d) Heat-treat the siliceous plant material at a certain temperature in the presence of oxygen, wherein the silica produced includes silica in a porous amorphous form.

22. A method for preparing porous amorphous silica from siliceous plant material containing non-siliceous inorganic substances, the method comprising the following steps: (a) By controlling the amount of the chelating agent, or by introducing an inorganic acid into the siliceous plant material, or by mixing a desired amount of a preselected non-siliceous inorganic substance into the siliceous plant material, the amount of at least one preselected non-siliceous inorganic substance in the siliceous plant material is manipulated so as to establish the amount of the preselected non-siliceous inorganic substance retained in the plant material at a preselected amount of 20 ppm to 25,000 ppm, the at least one preselected non-siliceous inorganic substance being selected from non-siliceous inorganic substances comprising lithium, potassium, sodium, calcium or magnesium, and the preselected amount of the at least one preselected non-siliceous inorganic substance being selected so as to control the surface area of the porous amorphous silica obtained after heat treatment within the range of 10 m 2 / g to 450 m 2 / g, the preselected non-siliceous inorganic substance including: elements or compounds of alkali metals, alkaline earth metals, aluminum, boron, iron, manganese, titanium and / or phosphorus; and b) Heat-treat the siliceous plant material at a temperature in the range of 200 °C to 1000 °C in the presence of oxygen, wherein the silica produced includes silica in a porous amorphous form.

23. The method of claim 22, wherein the amount of at least one preselected non-siliceous inorganic substance in the siliceous plant material is manipulated by controlling the amount of the chelating agent.

24. The method of claim 23, wherein the chelating agent is selected from citric acid, acetic acid, ethylenediamine, ethylenediaminetetraacetic acid, dimercaptosuccinic acid, trimethylamine tricarboxylic acid, α-lipoic acid, and diethylenetriaminepentaacetic acid.

25. The method of claim 24, wherein the amount of the chelating agent is from 0.001 kg per kg of plant material to 1 kg per kg of plant material.

26. The method of claim 25, wherein the chelating agent is citric acid, and the amount of citric acid is from 0.01 kg per kg of plant material to 0.1 kg per kg of plant material.

27. The method of claim 22, wherein the amount of at least one preselected non-siliceous inorganic substance in the siliceous plant material is manipulated by introducing an inorganic acid into the siliceous plant material.

28. The method of claim 27, wherein the at least one inorganic acid is selected from sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, boric acid, and perchloric acid.

29. The method of claim 22, wherein the amount of at least one preselected non-siliceous inorganic substance in the siliceous plant material is manipulated by mixing a desired amount of a preselected non-siliceous inorganic substance into the siliceous plant material.

30. The method of claim 22, wherein the surface area of the amorphous silica is controlled within a specific narrow band in the range of 10 m 2 / g to 450 m 2 / g by controlling the amount of the preselected non-siliceous inorganic substance in the siliceous plant material and the heat treatment temperature.

31. The method of claim 22, wherein the pore volume of the amorphous silica is controlled within a specific narrow band in the range of 0.50 cc / g to 0.05 cc / g by controlling the amount of the preselected non-siliceous inorganic substance in the siliceous plant material and the heat treatment temperature.

32. The method of claim 22, wherein the pore diameter of the amorphous silica is controlled within a specific narrow band in the range of 10 angstroms to 200 angstroms by controlling the amount of the preselected non-siliceous inorganic substance in the siliceous plant material and the heat treatment temperature.

33. The method of claim 22, wherein the amount of the non-siliceous inorganic substance in the siliceous plant material is controlled within the range of 300 ppm to 15000 ppm.

34. The method of claim 22, wherein the content of non-siliceous inorganic substances in the heat-treated silica is controlled within the range of 10 ppm to 1000 ppm by post-washing the silica with at least one of water, inorganic acid, chelating agent, and pH-adjusting chemical.

35. The method of claim 34, wherein the content of the non-siliceous inorganic substances in the heat-treated silica is controlled within the range of 100 ppm to 500 ppm by post-washing the silica with at least one of water, inorganic acid, chelating agent, and pH-adjusting chemical.

36. The method of claim 22, wherein the heat treatment temperature is within the range of 200 °C to 1000 °C.

37. The method of claim 22, wherein the preselected non-siliceous inorganic substances in the siliceous plant material include at least one of the following: lithium, sodium, potassium, magnesium, calcium, aluminum, boron, iron, manganese, titanium, or phosphorus.

38. The method of claim 22, wherein the content of the preselected non-siliceous inorganic substances in the siliceous plant material is chemically controlled.

39. The method of claim 22, wherein the content of the preselected non-siliceous inorganic substances and the heat treatment temperature are controlled to prevent the formation of a crystalline structure in the amorphous silica.

Citation Information

Patent Citations

  • Process for production of high purity amorphous silica from biogenic material

    US6406678B1

  • Process for recovering useful products and energy from siliceous plant matter

    US7270794B2

  • Process for recovering useful products and energy from siliceous plant matter

    US8057771B2